Dosis de pollinaza en el rendimiento de forraje Pennisetum sp. “cuba 22” en Loreto. 2023 - Musoline Acho, Jorge (2024)
In humid tropical areas such as the Loreto region, where the National University of the Peruvian Amazon is located with its faculty of agronomy that prioritizes research on pastures and forages, I carried out the present research work titled: “DOSE OF POLLINASE IN YIELD FORAGE Pennisetum sp. “CUBA 22” IN LORETO. 2023.” The cut-off time was 60 days with a Completely Randomized Block Design with 4 treatments and 4 repetitions. The treatments were T0 (0 tons of chicken manure/ha), T1 (10 tons of chicken manure/ha), T2 (20 tons of chicken manure/ha) and T3 (30 tons of chicken manure/ha), according to the results data in The dependent variables that were evaluated in the T3 treatment (30 tons of chicken manure/ha) are statistically equal to the T2 treatment (20 tons of chicken manure/ha) in all the dependent variables of the Cuba 22 forage research. Plant height (m) was 1.60 m. with T3 (30 tons of manure/ha). Regarding green and dry matter, it was 3.18 and 0.67 kg/m2. Regarding the green matter of leaves and green matter of stems of 0.80 and 2.39 kg/m2. Regarding the weight of bush/plant, 0.8 kg/plant was obtained. The yield of green matter kg/ha is 31,800 kg/ha.